The interaction between business models and business reality - Peter Kesting (Journal of Business Models (JOBM), 2021)
Purpose: The aim of this paper is to conceptualize the connection between business model and business reality. On this basis, the paper aims to put the business model on a solid conceptual basis and to build bridges to its neighbouring concepts. In this way, this paper should to contribute to more terminological and conceptual rigor of the business model construct. In addition, this paper aims to conceptualize the processes of constructing and using business models for decision-making. Design/Methodology/Approach: This is a conceptual paper; it introduces and specifies a new construct, the status quo, as real-world counterpart to the business model. Based on this, it develops a model of the interaction between business model and status quo. Findings: The key finding of this paper is that business model and status quo are shaped (and need to be described) by different characteristics. The characteristics of the status quo result from repetition (stability) and routinization (efficiency, low resistance, etc.). The characteristics of the business model result from observation, abstraction and simplification (purpose, observer perspective, etc.). Originality/Value: This is the first paper to develop the status quo as an independent construct for management research. It also offers the first comprehensive model of the relation between business model and business reality. Based on that, it allows establishing new connections between the business model concept and the theory of the firm, particularly with regard to innovation and routine.
Keywords: 650; business model; status quo; inertia; innovation; routine; theory of the firm